The relationship between nurses' risk assessment and management, fear perception, and mental wellbeing during the COVID-19 pandemic in Saudi Arabia - Al-Dossary, Reem N.; AlMahmoud, Sana; Banakhar, Maram Ahmed; Alamri, Majed; Albaqawi, Hamdan; Al Hosis, Khaled; Aljohani, Mohammed S.; Alrasheadi, Bader; Falatah, Rawaih; Almadani, Noura; Aljohani, Khalid; Alharbi, Jalal; et al. (Frontiers in Public Health, 2022)
During this pandemic, it is crucial to implement early interventions to help nurses manage their mental wellbeing by providing them with information regarding coping skills, preventive risk assessment approaches (such as hospital preparedness and rapid risk assessment), and the ability to respond. This study evaluated the effect of fear and risk assessment management on nurses' mental wellbeing during the COVID-19 pandemic in Saudi Arabia. A total of 507 nurses who worked in tertiary public hospitals were asked to take a descriptive design survey. Three survey scales were used to assess the survey: the Risk Assessment Scale, the Fear of COVID-19 Scale, and the Warwick-Edinburgh Mental Wellbeing Scale. Independent t-tests and a one-way ANOVA were used to examine the association between fear of COVID-19 and nurses' demographic characteristics on their mental wellbeing. A multiple regression analysis was performed to examine the predictors associated with mental wellbeing. Findings revealed that almost half of the participants showed moderate positive mental wellbeing, 49.7%, while only 14% had low levels of fear on the Warwick-Edinburgh Mental Well being Scale. Most of the respondents had low levels of fear on the Fear of COVID-19 Scale, 45%, while only 15% had high levels of fear on the scale. Then, some demographic variables, such as “age,” “nationality,” “total years of experience in the current hospital,” and “region you work at” had statistically significant differences with p < 0.5. Meanwhile, risk assessment is also associated with mental wellbeing scores. All items on the Fear of COVID-19 Scale showed no significant difference with a P > 0.05. In conclusion, most nurses providing direct patient care to a patient with COVID-19 emphasized the importance of wearing PPE and performing hand hygiene before and after any clean or aseptic procedure. Meanwhile, although almost all nurses were vaccinated, they were still afraid of a COVID-19 infection. Additionally, the results reported that the older the nurses are, the better their mental wellbeing scores. Non-Saudi nurses had higher perceived mental wellbeing scores than Saudi nurses, and different working environments corresponded to different mental wellbeing scores. Finally, nurses' risk assessment was associated with mental wellbeing scores.